2018
DOI: 10.1038/s41598-018-31833-4
|View full text |Cite
|
Sign up to set email alerts
|

Urate transporter inhibitor lesinurad is a selective peroxisome proliferator-activated receptor gamma modulator (sPPARγM) in vitro

Abstract: Gout is the most common arthritic disease in human but was long neglected and therapeutic options are not satisfying. However, with the recent approval of the urate transporter inhibitor lesinurad, gout treatment has experienced a major innovation. Here we show that lesinurad possesses considerable modulatory potency on peroxisome proliferator-activated receptor γ (PPARγ). Since gout has a strong association with metabolic diseases such as type 2 diabetes, this side-activity appears as very valuable contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 55 publications
1
16
1
Order By: Relevance
“…Differential binding modes within the FXR ligand binding site of FXR agonists OCA and MFA-1 15 , and differential effects of FXR agonists GW4064, CDCA and fexaramine on FXR regulated gene expression 16 already indicated several years ago, that FXR activation is more complex than just switched on or off. Later studies revealed that FXR ligands can differ in their recruitment profiles of various co-activators 17,18 , a characteristic that has also been observed for other NRs such as peroxisome proliferator-activated receptors 19,20 . Moreover, ivermectin 18 and structural analogues 21 were identified as specific FXR modulators that despite recruiting the NR co-repressor NCoR-2 to the FXR-LBD induced FXR-mediated reporter activity and gene expression, and recent results also point to an allosteric mechanism 22 of FXR activation by small molecules.…”
Section: Introductionmentioning
confidence: 71%
“…Differential binding modes within the FXR ligand binding site of FXR agonists OCA and MFA-1 15 , and differential effects of FXR agonists GW4064, CDCA and fexaramine on FXR regulated gene expression 16 already indicated several years ago, that FXR activation is more complex than just switched on or off. Later studies revealed that FXR ligands can differ in their recruitment profiles of various co-activators 17,18 , a characteristic that has also been observed for other NRs such as peroxisome proliferator-activated receptors 19,20 . Moreover, ivermectin 18 and structural analogues 21 were identified as specific FXR modulators that despite recruiting the NR co-repressor NCoR-2 to the FXR-LBD induced FXR-mediated reporter activity and gene expression, and recent results also point to an allosteric mechanism 22 of FXR activation by small molecules.…”
Section: Introductionmentioning
confidence: 71%
“…The results showed that SY could also increase PPARc2 mRNA levels in the adipocytes differentiated from the subcutaneous SVF, but not in the adipocytes differentiated from visceral SVF ( Figure S5c,d). These show that SY could be a novel PPARc agonist that might selectively activate PPARc2 in sWAT to improve insulin sensitivity, which could be similar to the selective PPARc modulators 41 . It was reported by Heitel et al 41 that selective PPARc modulators activated PPARc in a tissue-selectivity manner or differentially recruited coactivators to the nuclear receptor in different tissues.…”
Section: Discussionmentioning
confidence: 88%
“…Lesinurad (Fig. 1) is a medicine prescribed as a urate transporter inhibitor for treating hyperuricemia associated with gout (Heitel et al, 2018). The drug is a weak carboxylic acid (pK a = 3.2).…”
Section: Introductionmentioning
confidence: 99%